2017
DOI: 10.1026/0012-1924/a000177
|View full text |Cite
|
Sign up to set email alerts
|

Herausforderungen bei der Schätzung von Trends in Schulleistungsstudien

Abstract: Zusammenfassung. Internationale Schulleistungsstudien wie das Programme for International Student Assessment (PISA) dienen den teilnehmenden Ländern zur Feststellung der Leistungsfähigkeit ihrer Schulsysteme. In PISA wird die Zielpopulation (15-jährige Schülerinnen und Schüler) alle 3 Jahre getestet. Von besonderer Bedeutung sind dabei die Trendinformationen, die für die Zielpopulation ausweisen, ob sich ihre Leistungen gegenüber denen aus früheren Erhebungen verändert haben. Um solche Trends valide interpreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 14 publications
1
17
1
8
Order By: Relevance
“…At first sight, the finding of longer and more relevant responses seems contradictory to previous findings that tasks become more difficult on the computer (Kolen & Brennan, 2014;Robitzsch et al, 2017). However, a more detailed look at the variation of the effects across items puts this in a different light, in line with the inconsistent findings of mode effect studies.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…At first sight, the finding of longer and more relevant responses seems contradictory to previous findings that tasks become more difficult on the computer (Kolen & Brennan, 2014;Robitzsch et al, 2017). However, a more detailed look at the variation of the effects across items puts this in a different light, in line with the inconsistent findings of mode effect studies.…”
Section: Discussioncontrasting
confidence: 72%
“…The OECD acknowledges the possibility of potential small to medium mode effects for PISA 2015 . For Germany indeed, Robitzsch et al (2017) found a small mode effect. In line with the literature (e.g.…”
Section: Introductionmentioning
confidence: 91%
“…An exhaustive review of previous research is beyond the scope of this article. However, as Robitzsch et al.’s () results give reason to assume domain‐specific results, we present a more detailed review of previous results on the comparability of reading assessments.…”
Section: Previous Results On Mode Effects Of Reading Assessmentmentioning
confidence: 88%
“…The Programme for International Student Assessment (PISA) shifted to computer‐based testing in all domains in 2015 (OECD, ). Following the publication of the results, some authors found indications that cross‐sectional comparisons as well as the comparability of estimates to previous assessments (i.e., trend estimates) were probably influenced by the change from paper and pencil to computer tests ( mode effects ; e.g., Jerrim, Micklewright, Heine & Sälzer, ; Klieme, ; Komatsu & Rappleye, ; Robitzsch et al, ; see also Jerrim, ), calling into question whether potential mode effects were effectively handled in the procedures applied to the PISA 2015 cognitive measures.…”
mentioning
confidence: 99%
“…Since PISA introduced CBA in 2015 [18], some authors have questioned the comparability of CBA and PBA in PISA, in particular, concerning trend estimates (e.g., [19,20]). Although a detailed review of the current literature regarding mode effects is beyond the scope of this paper (see, e.g., [8]), we aim at providing a method for investigating response time differences between modes, which is currently missing.…”
Section: Invariance Of the Response Processes Between Gender And Modementioning
confidence: 99%